Sustainability in Public Lighting: The Methodology for Identifying Environmentally Optimal Solutions in Replacement Planning—A Case Study - Fabrizio Cumo; Elisa Pennacchia; Adriana Scarlet Sferra (Energies)
The urban public lighting system plays a fundamental role in enhancing safety and shaping the nocturnal identity of the city. Efficient lighting is also a key factor in reducing energy consumption and lowering atmospheric emissions. In the context of sustainable development goals, increasing attention is being directed towards the energy, social, economic, and environmental benefits associated with the adoption of LED lighting systems. This paper aims to assess the environmental impacts of two different public outdoor lighting replacement planning scenarios. The methodology employed in this study calculates the environmental impacts using a life cycle approach, incorporating data from the Environmental Product Declarations (EPDs) of the lighting systems. It involves a systematic census and categorization of lighting fixtures based on their installation year to determine both their quantity and average efficiency. This methodology, applied to a case study, demonstrates that it is possible to reduce the CO2-equivalent emissions by approximately 7% depending on the technical and environmental performance of the fixtures and the timing of their replacements. These results provide a scientific foundation for supporting both the preparation of planning tools by governance entities and the technical and economic feasibility of designing and implementing interventions aimed at improving the environmental performance of public lighting. These efforts could contribute to achieving climate neutrality, conserving biodiversity, and mitigating the effects of climate change.